Evaluation of comorbidity burden on disease progression and mortality in patients with interstitial pneumonia with autoimmune features: A retrospective cohort study. - Elena K Joerns; Michelle A Ghebranious; Traci N Adams; Una E Makris (PLoS ONE)
Background Interstitial pneumonia with autoimmune features (IPAF) is a subset of interstitial lung disease that manifests with features of autoimmunity while not meeting classification criteria for a defined rheumatic disease. Comorbidity burden is an important prognostic indicator in various rheumatic and interstitial lung diseases, but few studies have commented on comorbidities in this population. This study was conducted to evaluate the association of individual comorbidities, the Charlson Comorbidity Index (CCI), and the Rheumatic Disease Comorbidity Index (RDCI) with lung disease progression and transplant/mortality outcomes in patients with IPAF. Methods In a retrospective study, we evaluated the prevalence and severity of comorbidities in an institutional cohort of patients with IPAF. Using Cox regression, we correlated the association of individual comorbidities and comorbidity indices with time to lung disease progression (relative forced vital capacity decline of 10% or more) and with time to lung transplant/death. We compared the performance of CCI and RDCI in predicting outcomes. Results History of cerebrovascular accident (CVA) or cardiovascular disease (CVD), moderate-severe chronic kidney disease, and fracture was associated with a faster onset of lung disease progression, while a history of gastroesophageal reflux was protective. History of CVA/CVD, diabetes mellitus, and lymphoma were associated with a faster onset of lung transplant/death. Both CCI and RDCI were associated with shorter time to lung disease progression and lung transplant/death in unadjusted analyses. However, only CCI was associated with shorter time to lung transplant/death in analyses adjusted for age, sex, pulmonary function, and radiographic pattern of lung lesion. Conclusions CCI and RDCI may be useful tools in assessing prognosis in patients with IPAF in terms of both lung disease progression and mortality. Prospective studies are needed to further evaluate the performance of CCI and RDCI and the impact of optimizing comorbid conditions that may mitigate poor outcomes among patients with IPAF.